2019
DOI: 10.3390/ijerph16132409
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Built Environment in Person-Centred Rehabilitation at Home: Study Protocol

Abstract: Health services will change dramatically as the prevalence of home healthcare increases. Only technologically advanced acute care will be performed in hospitals. This—along with the increased healthcare needs of people with long-term conditions such as stroke and the rising demand for services to be more person-centred—will place pressure on healthcare to consider quality across the continuum of care. Research indicates that planned discharge tailored to individual needs can reduce adverse events and promote c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This study is part of a larger project called Rehabilitation and Architecture (REARCH) aiming to increase the knowledge of how the environment can facilitate and/or hinder person‐centred rehabilitation at home (Kylén et al., 2019). In REARCH we are working in partnership with persons with stroke, their organisations and several stroke units.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project called Rehabilitation and Architecture (REARCH) aiming to increase the knowledge of how the environment can facilitate and/or hinder person‐centred rehabilitation at home (Kylén et al., 2019). In REARCH we are working in partnership with persons with stroke, their organisations and several stroke units.…”
Section: Methodsmentioning
confidence: 99%
“…79,80 Future design considerations for stroke recovery should also extend to the home environment. 81…”
Section: Safety and Well-beingmentioning
confidence: 99%
“…Another innovative element of the program was also the help of a physiotherapist in reorganizing the home space in order to adapt it to the functional needs of the patient. The patient's environment may constitute a barrier or facilitation [23]; thus, eliminating barriers and maximizing facilitation allow the patients to get around better and to remain active in their environment [24]. Bethancourt et al showed that structural barriers (e.g., inadequate equipment) could hinder the physical activity of people with reduced fitness [25].…”
Section: Interventionmentioning
confidence: 99%